Theoretical Equations for the Ratio of Undrained Shear Strength to Vertical Effective Stress for Normally Consolidated Saturated Cohesive Soils: Theoretical Equations for the Ratio of Undrained Shear Strength to Vertical Effective Stress for Normally Consolidated Saturated Cohesive Soils - Sugeng Krisnanto (Jurnal Teknik Sipil, 2021)
Abstract Two theoretical equations are developed to calculate the ratio of undrained shear strength to the vertical effective stress (the ratio of (su/sv’)) for normally consolidated saturated cohesive soils. The effective stress approach is used as the basis in the development of the theoretical equations. The theoretical equations are developed by relating the total and the effective stress paths. The development of the excess pore-water pressure is quantified using Skempton A and B pore-water pressure parameters. The theoretical equations are developed for two initial stress conditions: (i) an initially hydrostatic condition and (ii) an initially Ko (non-hydrostatic) condition. The performance of the theoretical equations of this study is compared with field and laboratory measurement data obtained from the literature. The close results between the theoretical equations and the measurements show that the theoretical equations of this study can compute the ratio of (su/sv’) well. Using the theoretical equations, the values of the ratio of (su/sv’) commonly used in engineering practice can be explained from the soil mechanics framework. Keywords: Saturated cohesive soils, c/p ratio, normally consolidated soil, undrained shear strength, effective shear strength, theoretical equation. Abstrak Dua persamaan teoritis dikembangkan untuk menghitung rasio kuat geser tak teralirkan dengan tegangan efektif vertikal (rasio (su/sv’)) untuk tanah kohesif jenuh terkonsolidasi normal. Pendekatan tegangan efektif dijadikan dasar dalam pengembangan kedua persamaan teoretis ini. Persamaan teoretis tersebut dikembangkan menghubungkan lintasan tegangan total dan lintasan tegangan efektif. Kenaikan tekanan air pori ekses dikuantifikasi menggunakan parameter tekanan air pori A dan B dari Skempton. Persamaan teoretis dikembangkan untuk dua kondisi tegangan awal: (i) tegangan awal hidrostatik dan (ii) teganan awal Ko (non hidrostatik). Kinerja kedua persamaan teoretis tersebut dibandingkan terhadap data pengukuran lapangan dan pengujian laboratorium yang diperoleh dari literatur. Persamaan teoretis dari studi ini memiliki kinerja yang baik dalam memperhitungan rasio (su/sv’) yang ditunjukkan dengan dekatnya hasil perhitungan menggunakan persamaan teoretis dan hasil pengukuran lapangan maupun pengujan laboratorium. Dengan persamaan teoretis tersebut, nilai rasio (su/sv’) yang biasa digunakan dalam rekayasa praktis bisa dijelaskan secara mekanika tanah. Kata-kata Kunci: Tanah kohesif jenuh, rasio c/p, tanah terkonsolidasi normal, kuat geser tak teralirkan, kuat geser efektif, persamaan teoretis.